Irritable bowel syndrome. Nutritional and lifestyle risk factors in a Norwegian population - Pettersen, Stian Aleksander (Universitetet i Tromsø, 2013)
Objective: To study potential lifestyle and nutritional risk factors for irritable bowel syndrome (IBS) in an adult northern Norwegian population. In addition, report on some of the known risk factors for IBS in this population. Materials and methods: In 2007, 19 762 adults (aged 30-87) from the municipality of Tromsø in Northern Norway, were invited to attend a general health survey. A total of 12 984 (65.7%) subjects accepted the invitation and answered the first visit questionnaires upon which this report is founded. Dietary and lifestyle, as well as some comorbidity risk factors for IBS were explored in a logistic regression model. Results: A total of 7 063 subjects (54.4%) reported having “some or more” abdominal pain or discomfort during the last 12 months. When applying Rome II criteria for IBS, we find a population prevalence of 8.4% with a female predominance and age-dependent decrease. Factors that influence IBS with statistical significance in a multivariate regression model were male gender (OR 0.55), age 50-59 years (OR 0.79), age 60-69 years (OR 0.75), age ≥70 years (OR 0.71), psychological/psychiatric problems (OR 1.78), hypothyroidism (OR 1.37), exercising more than 4 hours per week (OR 0.79), eating breakfast daily (OR 1.33) and drinking fruit juice daily (OR 1.24). Our model could only explained 4% of the variability of IBS. Asthma, diabetes, being overweight or obese, daily coffee consumption, weekly alcohol, weekly fish (neither lean nor fat) and eating warm dinner more than 5 times per week, did not show statistical significance in affecting the variability of IBS in our model. Conclusion: IBS is prevalent in an urban Norwegian population. Female gender, young age, psychological problems, hypothyroidism, eating breakfast daily, drinking fruit juice daily are significant risk factors for IBS, although they explain only 4% of the variability of IBS. Male gender and physical activity in excess of 4 hours per week was significantly negatively associated with IBS.